1991
DOI: 10.2307/1130811
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Understanding of Other People's Feelings and Beliefs: Individual Differences and Their Antecedents

Abstract: Individual differences in young children's understanding of others' feelings and in their ability to explain human action in terms of beliefs, and the earlier correlates of these differences, were studied with 50 children observed at home with mother and sibling at 33 months, then tested at 40 months on affective-labeling, perspective-taking, and false-belief tasks. Individual differences in social understanding were marked; a third of the children offered explanations of actions in terms of false belief, thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

52
560
4
19

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 695 publications
(635 citation statements)
references
References 17 publications
52
560
4
19
Order By: Relevance
“…An age-related increase is expected to be more marked in body-related events, as young children's tendency to reason in concrete terms may limit their spontaneous ability to connote physical events by making reference to psychological states. Although some studies showed girls' superior comprehension and production of affective mental states (Brown, Donelan-McCall, & Dunn, 1996;Dunn et al, 1991;Fivush, Brotman, Buckner, & Goodman, 2000), gender was not significant when 3-yearolds (Fivush & Wang, 2005) and 5-to-12-year olds talked about personal events. Thus, in the present study we looked at whether the use of psychological lexicon would vary with gender, depending on age and event domain.…”
Section: Studymentioning
confidence: 96%
See 1 more Smart Citation
“…An age-related increase is expected to be more marked in body-related events, as young children's tendency to reason in concrete terms may limit their spontaneous ability to connote physical events by making reference to psychological states. Although some studies showed girls' superior comprehension and production of affective mental states (Brown, Donelan-McCall, & Dunn, 1996;Dunn et al, 1991;Fivush, Brotman, Buckner, & Goodman, 2000), gender was not significant when 3-yearolds (Fivush & Wang, 2005) and 5-to-12-year olds talked about personal events. Thus, in the present study we looked at whether the use of psychological lexicon would vary with gender, depending on age and event domain.…”
Section: Studymentioning
confidence: 96%
“…Moreover, family discourse exposes young children to event discussions in which the child's or other people's behaviours and internal states are involved (e.g. Dunn, Brown, Slomkowski, Tesla, & Youngblade, 1991;Fivush & Nelson, 2006;Reese & Fivush, 1993;Ruffman, Perner, & Parkin, 1999;Vinden, 1997). Thus, we expected children to be more likely to reason on the causes of events such as psychological events and accidents in which people's behaviour plays a direct role, rather than events involving illness, where causes are often not dependent on one's behaviour.…”
mentioning
confidence: 99%
“…Esta perspectiva de la intersubjetividad se ha complementado de forma muy acertada, con los estudios longitudinales realizados por investigadores como Dunn, Brown, Slomkowski, Tesla & Youngblade (1991). Estos estudiosos han demostrado que existen variables asociadas al desarrollo de la TdM, como son las habilidades lingüísticas.…”
Section: La Intersubjetividad Y La Perspectiva De La Segunda Personaunclassified
“…Estos estudiosos han demostrado que existen variables asociadas al desarrollo de la TdM, como son las habilidades lingüísticas. El desarrollo del lenguaje y la exposición a conversaciones con contenido mental predicen, en efecto, posteriores niveles de ejecución en tareas de TdM (Astington & Jenkins, 1999;Slade & Ruffman, 2005;Dunn, et. al., 1991).…”
Section: La Intersubjetividad Y La Perspectiva De La Segunda Personaunclassified
See 1 more Smart Citation